Radiotherapy 2017
DOI: 10.5772/67445
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Radiotherapy for Lung Cancer Using Uniform Scanning Proton Beams

Abstract: Lung cancer remains the leading cause of cancer death in North America and is one of the major indications for proton therapy. Proton beams provide a superior dose distribution due to their finite ranges, but where they stop in the tissue is very sensitive to anatomical change. To ensure optimal target coverage and normal tissue sparing in the presence of geometrical variations, such as tumor shrinkage and other anatomical changes, adaptive planning is necessary in proton therapy of lung cancer. The objective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Stuschke et al, also reported that IMPT was advantageous in terms of lung sparing compared to both Tomotherapy and IMRT [7]. The dosimetry of USPT for lung cancer was similar to PSPT, as reported by Zheng [14].…”
Section: Introductionmentioning
confidence: 60%
“…Stuschke et al, also reported that IMPT was advantageous in terms of lung sparing compared to both Tomotherapy and IMRT [7]. The dosimetry of USPT for lung cancer was similar to PSPT, as reported by Zheng [14].…”
Section: Introductionmentioning
confidence: 60%
“…The advent of US-PT allowed for more precise proton delivery by enabling dose deposition in successive layers using scanning magnets, resulting in a more conformal dose distribution compared with that achievable with PS-PT (8). However, US-PT is still limited to the use of only a single beam energy per layer, without the option of energy modulation during dose delivery of each layer.…”
mentioning
confidence: 99%